Collisional excitation of interstellar PO(X2Π) by He: new ab initio potential energy surfaces and scattering calculations. Issue 8 (25th September 2017) - Lique, François; Jiménez-Serra, Izaskun; Viti, Serena; Marinakis, Sarantos
Abstract : The inelastic scattering of PO (X, v = 0) has been investigated by quantum scattering calculations using a new potential energy surface. Abstract : We present the first ab initio potential energy surfaces (PESs) for the PO(X 2 Π)–He van der Waals system. The PESs were obtained using the open-shell partially spin-restricted coupled cluster approach with single, double and perturbative triple excitations [UCCSD(T)]. The augmented correlation-consistent polarized valence triple-zeta (aug-cc-pVTZ) basis set was employed supplemented by mid-bond functions. Integral and differential cross sections for the rotational excitation in PO–He collisions were calculated using the new PES and compared with results in similar systems. Finally, our work presents the first hyperfine-resolved cross sections for this system that are needed for accurate modelling in astrophysical environments.